Developing Canva-Based Interactive Learning Media Integrating Education for Sustainable Development for Ecosystem Learning in Senior High School - Vina Auliya Sari; I Made Sutajaya; Ida Ayu Purnama Bestari; Desak Made Citrawathi; Ni Putu Sri Ratna Dewi (IAIN Sorong, 2026)
Biology learning on ecosystem material is still dominated by conventional media such as printed textbooks and static PowerPoint, causing low interactivity and minimal integration of Education for Sustainable Development (ESD) values. This study aims to produce a design of interactive Canva learning media on ecosystem material oriented to ESD for 10th-grade students, and to analyze its validity and practicality. This study used Research and Development (R&D) with the ADDIE model, limited to the analyze, design, and development stages. Validity was assessed by two content experts and two media experts using a Likert-scale questionnaire analyzed through Pearson Product Moment correlation, while practicality was assessed by three teachers and 34 students using descriptive percentage analysis. The results show that the media design consists of introduction, core, and closing sections integrating the ESD stages of know, feel, think, and action. The validity test produced correlation coefficients of 0.644 and 0.819 (content aspect) and 0.828 and 0.792 (media aspect), all with p < 0.05, indicating valid and significant results. The practicality test showed 93.8% (teachers) and 91% (students), both in the very practical category. These findings imply that Canva can be transformed from a static design tool into a comprehensive, ready-to-use interactive learning medium that supports contextual and sustainability-oriented biology instruction.